Low-Cost Adsorbent Development: Sulfuric Acid-Activated Teak Sawdust for Effective Methylene Blue Removal - Baunsele, Anselmus Boy; Missa, Hildegardis; Siswanta, Dwi; Naat, Johnson N.; Neolaka, Yantus A. B.; Nitti, Fidelis; Lema, Abner Tonu; Basuki, Rahmat; Rahayu, Rahayu (Jurnal Kimia Valensi, 2024)
The expansion of the global textile industry has resulted in a decline in environmental quality. Environmental pollution resulting from textile dye waste may include heavy metals and dyes, which exhibit carcinogenic and mutagenic effects. Many studies have been done to reduce the harm of dyes. Extensive research has been undertaken to mitigate the detrimental effects of dyes. One cost-effective approach for managing dye pollution is the adsorption of methylene blue using sulfuric acid-activated teak sawdust. Teak wood sawdust, a byproduct of the furniture industry that is abundant and underutilized, contains active sites within its constituent compounds, including cellulose, hemicellulose, and lignin. This study was designed to determine the ability of teak sawdust to adsorb methylene blue. In this investigation, the biosorbent will be characterized using fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and scanning electron microscopy-energy dispersive X-ray (SEM-EDX) to analyze its active sites and surface morphology. Additionally, the study aimed to elucidate the impact of variation contact time, pH solution, and alteration in methylene blue concentration on the adsorption capacity for methylene blue, employing a UV-Vis spectrophotometer for measurement. The research results demonstrated that optimal adsorption occurred at a contact time of 30 minutes and a pH of 6, with the adsorption efficiency reaching 99.67% as a function of contact time. The kinetic study was modeled using a pseudo-second-order approach, with a kinetic constant of 79.71 g mg⁻¹ min⁻¹. The maximum adsorption capacity was 1.351 mg g⁻¹, the n value was 1, and the percentage of methylene blue adsorbed reached 99.88%.